2009
DOI: 10.1016/j.jacc.2009.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Magnetic Resonance Imaging for Atherosclerosis Therapeutic Evaluation

Abstract: Multicenter, randomized, placebo-controlled "outcome" trials with long-term follow-up of thousands of patients are currently being used to evaluate new therapies for cardiovascular disease. Owing to improvements in risk factor modifications as well as to the concomitant use of established treatments, such as statins, leading to a drop in clinical event rates, it is projected that the number of patients enrolled in trials may need to be increased to separate the effect of new therapies from those of established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…The iron oxide based NPs are shown to be generally safe in animals and humans (9, 40). However, recently some concerns have been raised regarding the possible side effects of these particles (10).…”
Section: Discussionmentioning
confidence: 99%
“…The iron oxide based NPs are shown to be generally safe in animals and humans (9, 40). However, recently some concerns have been raised regarding the possible side effects of these particles (10).…”
Section: Discussionmentioning
confidence: 99%
“…Since macrophage uptake can correlate to the rate of lesion growth and its instability, it may be a particularly useful marker. 132, 133 …”
Section: Tracking the Distribution Of Polymeric Micellesmentioning
confidence: 99%
“…Previous studies have demonstrated USPIO particles can be used effectively to image atherosclerosis [6]; however, in the United States these particles are not yet approved for clinical use by the Food and Drug Administration [7], despite the fact that similar compounds have been in development for years [8]. Given the widespread availability of 18 FDG, 18 FDG-based PET imaging of plaque metabolism/inflammation may predominate for molecular imaging of large-artery atherosclerosis pharmacotherapy, at least in the near term.…”
Section: Commentsmentioning
confidence: 99%